Potential mechanisms of action and effectiveness of electroconvulsive therapy in the treatment of depressive disorders - Smulewicz, Klaudia; Wójcik, Alicja; Pakaszewski, Wojciech; Rusin, Bartosz; Ziomko, Bartłomiej (Journal of Education, Health and Sport, 2022)
The aim of this study is to prove the positive effect of electroconvulsive therapy on depressive disorders. Depression as a mental illness has not been fully studied in terms of its relationship in combination with electroconvulsive therapy. Nevertheless, despite many uncertainties, its positive effect on this type of treatment is indicated. Analysing a number of studies, electroconvulsive therapy is considered to be the most effective treatment for depression. As the research work shows, thanks to the use of electroconvulsive therapy in older people over 60 years of age, a positive effect on the patient’s health can be observed in the entire study group. The mechanism of action of electroconvulsive therapy is multifaceted. There are several theories of how it works, affecting different areas of the individual’s body. These include an anticonvulsant theory (GABAergic), effects on serotonergic and dopaminergic functions in the brain, effects on neurogenesis in the hippocampus and amygdala and neuropathicity, effects on gene transcription, an increase in the Narp protein with a presumed antidepressant effect, support for the neuroendocrine mechanism, as well as effects on inflammation (cytokines).